2014
DOI: 10.1002/2014gl061233
|View full text |Cite
|
Sign up to set email alerts
|

Liquid iron‐sulfur alloys at outer core conditions by first‐principles calculations

Abstract: We perform first-principles calculations to investigate liquid iron-sulfur alloys (Fe, Fe 56 S 8 , Fe 52 S 12 , and Fe 48 S 16 ) under high-pressure and high-temperature (150-300 GPa and 4000-6000 K) conditions corresponding to the Earth's outer core. Considering only the density profile, the best match with the preliminary reference Earth model is by liquid Fe-14 wt % S (Fe 50 S 14 ), assuming sulfur is the only light element. However, its bulk sound velocity is too high, in particular in the deep outer core,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 25 publications
3
45
1
Order By: Relevance
“…A temperature effect on the V P of liquid Fe‐C was not found in the recent laser‐heated DAC study performed by Nakajima et al []. Theoretical calculations at core pressures have also suggested that the sound velocities of liquid Fe and Fe‐S alloys are not sensitive to temperature [ Vočadlo et al , ; Ichikawa et al , ; Umemoto et al , ].…”
Section: Sound Velocity and Density Of Liquid Fe‐ni‐s At High P‐tsupporting
confidence: 91%
See 2 more Smart Citations
“…A temperature effect on the V P of liquid Fe‐C was not found in the recent laser‐heated DAC study performed by Nakajima et al []. Theoretical calculations at core pressures have also suggested that the sound velocities of liquid Fe and Fe‐S alloys are not sensitive to temperature [ Vočadlo et al , ; Ichikawa et al , ; Umemoto et al , ].…”
Section: Sound Velocity and Density Of Liquid Fe‐ni‐s At High P‐tsupporting
confidence: 91%
“…The shaded areas around curves show the uncertainties of the extrapolations (see text for detail). The open and closed squares indicate the sound velocities of liquid Fe 75 S 25 [ Umemoto et al , ] and Fe 75 S 25 [ Badro et al , ].…”
Section: Implications For the Core Composition Of Earth And Eventualmentioning
confidence: 99%
See 1 more Smart Citation
“…Density measurements on liquid Fe-Ni-S alloys demonstrated that the Earth's outer core composition with 19.2 at. However, its bulk sound velocity is much higher than the seismic observation in particular in deep outer core, suggesting other light elements on top of S [Umemoto et al, 2014]. Recent first-principle calculation supports this estimate of S content in the outer core.…”
Section: Resultsmentioning
confidence: 58%
“…We have also estimated the amount of other light elements including hydrogen, carbon, oxygen, silicon, and sulfur required to explain the ρ and V P observations of the Earth's outer core (Badro et al, 2014;Umemoto et al, 2014;Umemoto & Hirose, 2015; Figure 3). We determine the light element content in the outer core with the formalism: Δρ ð Þ FeÀCMB ¼ dρ dX ÂX ρ (mol %) where X ρ is the mol % of light element required to match the observed density and ΔV P ð Þ FeÀCMB ¼ dVP dX À Á ÂX VP (mol %), where X VP is the mol % of light element required to match the observed P wave velocity (V P ).…”
Section: Discussionmentioning
confidence: 99%